Dye-Sensitized Solar Cell Photoelectrochemical Tandem System Performance Study: TiO2 Nanotube/N719, BiVO4/TiO2 Nanotube, Ti3+/TiO2 Nanotube for Nitrogen Reduction Reaction to Ammonia - Suharyadi Suharyadi; Muhammad Iqbal Syauqi; Prita Amelia; Yunita Yunita; Jarnuzi Gunlazuardi (Indonesian Journal of Chemistry, 2023)
Ammonia is commonly synthesized through the Haber-Bosch process, which produces large amounts of CO2 emissions as it is carried out at extreme temperatures and pressures. An alternative technology is needed to synthesize ammonia which consumes less energy and is environmentally friendly. In this research, a Dye-Sensitized Solar Cell Photoelectrochemical tandem system (DSSC-PEC) was developed for the nitrogen reduction reaction (NRR) into ammonia. PEC cells utilized BiVO4/TiO2 Nanotube (BiVO4/TiO2NT) as a photoanode for water oxidation. BiVO4/TiO2NT was synthesized by the successive ionic layer adsorption and reaction (SILAR) with the cycles variation of 10, 15, and 20 cycles. The optimization method for 20 cycles (20s) gave the highest photocurrent of 0.352 mA/cm2. As a cathode where the nitrogen reduction reaction to ammonia takes place, Ti3+/TiO2NT was used. DSSC based on TiO2NT/N719 with an efficiency of 1.13% was used as an energy booster in the reaction. Using this system with an electrodes area of 3 cm2, under visible light irradiation on photoanode and DSSC while dark at the cathode, the rate of ammonia production, analyzed using the phenate method was 0.022 µmol.h−1.cm−2 with solar to chemical conversion (SCC) efficiency of 0.003%.